PENERAPAN MODEL DISCOVERY LEARNING UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS XI MIA 5 MAN 2 MODEL PEKANBARU - Refika Sari; Sehatta Saragih; Kartini Kartini (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This research was using class action research. This research aims to fixed the process of learning and improve learning result in mathematics in grade XI MIA 5 of MAN 2 Model Pekanbaru by applying the Discovery Learning model. The subject of this research were the students in the class XI MIA 5 of MAN 2 Model Pekanbaru that consist of 10 boys and 16 girls at the second semester of academic year 2016/2017. During the learning process, there is a problem of learning that is still focused on the teacher so that students can not find the concept of learning. To solve this problem requires a learning model where students can actively discover their own learning concepts. The instruments of data collection in this research were observation sheets and students mathematics tests. The observation sheets were analyzed in desciptive narative, meanwhile the students’ mathematic tests were analyzed in statistic desciptive. Based on the analysis showed that an improvement of learning process prior to the action on the first and second cycles and improve the students’ in the second semester academic years 2016/2017. Based on the result of research, the implementation of discovery learning methods can fix the learning process and improving student’s achievement of learning mathematisc in grade XI MIA 5 of MAN 2 Model Pekanbaru.Keywords : Students’ Math Achievement, Discovery Learning Model, Clasroom Action Research.